Universal and Culture-Specific Features of the Labour Concept in English and Uzbek Idioms: A Cognitive-Linguistic Perspective - Juraev Ganisher Alisherovich (International Journal of Literature and Language Studies, 2026)
Abstract. This article examines the concept of LABOUR/MEHNAT as verbalized in English and Uzbek idiomatic expressions within the framework of cognitive linguistics and cultural linguistics. Through comparative analysis of phraseological units, the study identifies both universal cognitive mechanisms (conceptual metaphors, metonymies) and culture-specific (linguocultural) features that distinguish the English individualistic work ethic from the Uzbek collectivist and spiritually grounded perception of labour. The findings contribute to the understanding of how cultural worldviews are encoded in figurative language.